2022
DOI: 10.4081/jphia.2022.2225
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices of female students at University of Kara regarding sexually transmitted infections in Togo, 2021

Abstract: A good knowledge of sexually transmitted infections (STI) in female students is an important element in the prevention of STI transmission. The objective of this study is to describe the level of knowledge and practices on STI among female students at the University of Kara. A cross-sectional study was conducted at the University of Kara from July to September 2021. Data were collected using a standard, digitalised, selfadministered questionnaire. Logistic regression analysis was used to describe factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This phenomenon of totally lacking an understanding of sexually transmitted infections is a manifestation of a lack of relevant education. Some previous studies have shown that a lack of STI-related knowledge might lead to insufficiencies in the awareness required to take preventive measures against STIs [ 19 , 20 ]. When people do not know about the routes of transmission of STIs or their symptoms, they cannot take effective preventive measures, nor can they seek timely medical treatment in the early stages of the disease in order to prevent its subsequent progression.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon of totally lacking an understanding of sexually transmitted infections is a manifestation of a lack of relevant education. Some previous studies have shown that a lack of STI-related knowledge might lead to insufficiencies in the awareness required to take preventive measures against STIs [ 19 , 20 ]. When people do not know about the routes of transmission of STIs or their symptoms, they cannot take effective preventive measures, nor can they seek timely medical treatment in the early stages of the disease in order to prevent its subsequent progression.…”
Section: Resultsmentioning
confidence: 99%
“…We did not include perceived severity and response efficacy in our analysis as another study found that these factors are not effective in changing behaviors related to STI prevention education (12). Although knowledge is not a construct of PMT, it was evaluated alongside the main constructs of this theory since increasing knowledge and awareness about STIs can be an effective component in promoting self-protection against STIs (10,30). By providing individuals with accurate information about STIs and their transmission, they can make informed decisions about their behaviors and take steps to reduce their risk of infection.…”
Section: Conceptual Frameworkmentioning
confidence: 99%